Penerapan Keteladanan dalam Pembentukan Akhlak Terpuji pada Anak Usia 5-6 Tahun Di TK Aisyiyah Bustanul Athfal - Duriani; Jannah, Ghina Raudhatul; M. Shabir U; M. Yusuf T; Kustiah, Sri (Early Childhood Islamic Education, 2024)
The role of teachers is very important not only in stimulating children's cognition but also in terms of being role models to shape the character of students so that they have commendable morals. This study aims to describe the application of teacher exemplary methods in the formation of commendable morals of students at Aisyiyah Bustanul Athfal Minasa Upa Kindergarten. This study uses a qualitative approach with a case study type. Data were collected through student observations and interviews with teachers. The focus of the study is on the application of teacher exemplary methods in everyday life in the school environment. Data analysis uses descriptive. The study results indicate that applying teacher exemplary methods at Aisyiyah Bustanul Athfal Minasa Upa Kindergarten is implemented through various habituation programs integrated into daily activities. The program includes the habit of praying on time in the congregation, speaking well and politely to friends and teachers, maintaining cleanliness and tidiness of oneself and the school environment, instilling an attitude of helping each other in everyday life, and cultivating an attitude of forgiving each other to create harmonious relationships. In addition, commendable moral values ​​such as honesty, responsibility, patience, discipline, and respect for others are also instilled through consistent role models from teachers. These programs are designed not only to shape the character of students with commendable morals but also to create a conducive school atmosphere as a learning environment based on moral and spiritual values.